Magnetic Field Measurement Using Peak-Locked Zeeman Coherent Population Trapping Resonance in Rubidium Vapor - Renu Tripathi; Gour S. Pati (IEEE Photonics Journal)
A sensor for magnetic field measurement is developed using a small (centimeter size) rubidium cell. A high contrast Zeeman coherent population trapping (CPT) resonance is produced by the magnetic dither in the sensor solenoid, and a peak-locked servo is implemented for magnetic field measurement. Sensitivity close to $\text{110 pT}/\sqrt {\text{Hz}} $ has been achieved in axial field measurement. The CPT-based magnetic sensor is capable of measuring sub-nanotesla level magnetic field variations at high (microtesla) field strength. We discussed possible sources of noise and broadening which are affecting the performance of the sensor, and suggest changes that will further improve the performance of the sensor.